Perkembangan Musik Talempong Duduak Di Sanggar Seni Puti Tungga Kabupaten Dharmasraya - Shelvy Alvionita; Esy Maestro (SENDRATASIK UNP, 2020)
The tradition of talempong music has been hereditary into a part of the Minangkabau social life. In its journey, traditional art has been in contact with the sharing of symptoms that develop in the life of a dynamic society, based on it, there also emerged the genre of talempong creation in the Minangkabau region. Puti Tunggastudioplays talempong with the type of talempong duduak (diatonic). The form of the talempong duduak performance is usually combined with several modern instruments such as electric guitar, sexophone, drums and also other traditional Minangkabau musical instruments. The purpose of this study is to analyze the development of talempong duduak music at Puti Tungga Studio in Dharmasraya Regency. Type of this research was qualitative with using a descriptive analysis approach. The object of this research was Talempong in the Pulau Punjung sub-district, Dharmasraya Regency. Techniques of data collection were done by using library studies, observations, interviews and documentation. Efforts that are done by Puti Tungga Studio for the development of the Talempong Duduak are such as gathering members, training in a week and being active in the appearance of the Talempong Duduak in Dharmasraya. There are several obstacles found by Puti Tungga Studio in developing the Talempong Duduak , such as the players who often change because of their busy activities, the higher flow of modern music and the high interest of the society towards modern music. The development and preservation of the Talempong Duduak musical instrument currently needs to be done by socializing to the wider society, especially the younger generation through the Department of Education by incorporating traditional art knowledge both in theory and practice into the curriculum through elementary school to senior high school level.